Does the use of Location in a Brand's Identity Contribute to its Brand Equity? - Bester, Karna (The IIE, 2016)
The research conducted focused on investigating what the impact of location within a brand’s identity is on brand equity. Trough conducting a mixed methods research a case study was done on the clothing brand “Stellies”. Quantitative data was collected in order to gain people’s perceptions and associations of the brand. This data showed that Stellies was mostly associated with university life. Quantitative data collected depicted individuals views on what the associating attributes of Stellenbosch is. These attributes showed Stellenbosch to be a town with rich history, part town and a university town. The associations with Stellenbosch and The clothing brand was directly matched to each other in order to understand if the location has an influence on how the brand identity is perceived. In order to understand if this case was contributing to brand equity Keller’s model was applied. The model helped gain insight on the fact that the locations influence did indeed influence the brands equity.
Keywords: Brand identity; Location